Hubungan Perilaku Perawatan Kaki Dengan Terjadinya Komplikasi Diabetic Foot Ulcer Pada Pasien DM Tipe 2 Di RSUD Pagelaran Cianjur Tahun 2023 - Siti Salsa Antik Maretna; Erna Safariyah; Sri Kurnia Dewi (Pusat Riset dan Inovasi Nasional, 2024)
Diabetes Mellitus is a chronic disease characterized by an increase in blood sugar levels, the cause of which is unhealthy lifestyle behavior, lack of physical activity and stress, which can cause various chronic complications. A complication that is often found in sufferes with type 2 diabetes melilitus is diabetic foot ulcers which are open wounds on the surface of the skin of the feet. A further impact of diabetic foot ulcers is amputation. Prevention that can be done for these complications is to have good foot care behavior. Objective: Tis study was to determine the relationship between foot care behavior and the event of complications of diabetic foot ulcers in RSUD Pagelaran Cianjur. Methods: This study used analytic descriptive quantitative method with Cross-sectional technique with 30 respondents. Results: Based on the results of the analysis using the Chi-square statistical test obtained p = 0,000 < α = 0,05 then Ha is accepted, which means there is a relationship between foot care behavior and the event of complications of diabetic foot ulcers in patients whit type 2 diabetes mellitus in RSUD Pagelaran Cianjur . Conclusion: That there are is a significant relationship between foot care behavior and the event of complications of diabetic foot ulcers in patients whit type 2 diabetes mellitus in RSUD Pagelaran Cianjur. Suggestion: It is hoped that good foot care behavioe will be maintained by patients with type 2 diabetes mellitus so that complications of diabetic foot ulcesr can be prevented